SHARIA MICROFINANCE REFORMULATION TOWARDS AN INCLUSIVE ECONOMY: An Approach Maqashid al-Shariah fi Hifdz al-Mal - Ubaidillah; Nurrohman, Dede; Anshor, Ahmad Muhtadi (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
Economic inequality and high poverty rates remain crucial issues in many Muslim-majority countries. This is due to the unequal distribution of wealth, the low quality of public services, and the suboptimal utilization of Islamic economic instruments such as zakat and waqf. Sharia microfinance has emerged as a fair and inclusive financing solution. However, the current model tends to imitate conventional systems and does not fully reflect the values of maqasid al-shariah, particularly in the aspect of hifdz al-mal (protection of wealth). This research aims to rebuild the Sharia microfinance model based on maqashid al-shariah fi hifdz al-mal as an ethical and normative basis for creating an Islamic financial system that is fair, sustainable, and relevant to contemporary socio-economic challenges. Using an Islamic legal research case study approach, this research examines the principles of Islamic financial management, critiques the weaknesses of existing microfinance models, both conventional and Sharia-compliant, and proposes more comprehensive design alternatives. Primary data for this study were obtained through field surveys, in-depth interviews, and direct observation at several Sharia Microfinance Institutions and beneficiary communities. The research results indicate that the application of maqashid al-shariah in the context of asset protection can strengthen the contribution of Islamic financial institutions to empowering micro, small and medium enterprises, alleviating poverty, and achieving the Sustainable Development Goals (SDGs). The proposed model emphasizes the principles of justice, spiritual and material well-being, protection of fundamental rights, and institutional synergy based on Islamic values.